Explore the relationship between human resource management practices and the consequences for emotional labor of insurance agents in the Jordanian insurance industry - Asaad Ahmad abdelqader Alsakarneh (Taylor & Francis Group, 2018)
The aim of this paper is to explore the relationship between human resource management practices and the consequences for the emotional labor of insurance agents in the Jordanian insurance industry. Many work positions require employees to demonstrate enthusiastic responses to customers, partners, or directors; however, these required responses occasionally or frequently negate the actual sentiments of employees. Enthusiastic work responses may be required, particularly in administration occupations, where association with other individuals is a substantial part of the job. The sample population for this review comprised 28 insurance agencies in Jordan. Data were collected by questionnaire; the final number of usable survey forms was 193, with a response rate of 64.3%. Results show that the popularity levels of controlling enthusiastic responses are identified with a few undesired mental results, for example, push and compassion fatigue. This finding suggests plans for work positions and highlights the significance of applying appropriate procedures in hiring and training employees.